Karakteristik Pasien Geriatri dengan Osteoarthritis Genu yang Mendapatkan Terapi Rehabilitasi Medik di Rumah Sakit Ibnu Sina Pada Tahun 2024 - Rifkah Tul Mukarramah Danial; Imran Safei; Iin Widya Ningsi; Fadil Mula Putra; Muh. Jabal Nur (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Knee osteoarthritis is a degenerative joint disease that commonly affects older adults and causes pain and functional limitations. Age, obesity, a sedentary lifestyle, and comorbidities influence disease severity and response to medical rehabilitation. This study aimed to describe the characteristics of geriatric patients with knee osteoarthritis receiving medical rehabilitation therapy at Ibnu Sina Hospital, Makassar, in 2024. This was a quantitative descriptive study with a cross-sectional design. The results showed that most geriatric patients with knee osteoarthritis undergoing medical rehabilitation at Ibnu Sina Hospital in 2024 were in the 60–70 year age group and were predominantly female. The majority of patients had a body mass index in the overweight to obese category. Most patients had no history of smoking but had one or more comorbidities, particularly hypertension and diabetes mellitus. Medical rehabilitation therapy was generally provided as a combination of several modalities. In conclusion, geriatric patients with knee osteoarthritis receiving medical rehabilitation were predominantly aged 60–70 years, female, overweight or obese, and had comorbidities. These findings highlight the importance of individualized and multidisciplinary rehabilitation approaches based on patient characteristics